Cooperation and Its Influence on Solidarity toward Mothers of Children with Autism - García Mejía, Eliana Aracely (Espergesia, 2025)
Mothers of children with autism face challenges in their daily lives that are invisible and need support; cooperation is presented as fundamental in strengthening solidarity towards these mothers; therefore, it is essential to give visibility to their experiences, given their care work. The general objective was to determine cooperation and its impact on solidarity with mothers of children with autism in the multisensory room of the Manta canton 2023-24. A qualitative approach was applied, with a Hermeneutical Phenomenological design, based on the theory of Cooperation, using techniques such as participant observation, documentary analysis and semi-structured interviews. The type of sample was voluntary participation, a semi-structured interview was conducted with 14 mothers who attend the Multisensory Room. The results determined that through inter-institutional cooperation, the operation of the Multisensory Room can be optimized, although some challenges remain; Support networks have limitations and need more awareness, while reciprocity between mothers helps in the care of children, but formal spaces are necessary. It is concluded that is cooperation between institutions, mothers and families has an essential role in supporting children with autism and their caregivers, but even so it is necessary to continue working on the inequality, availability and quality of each of these services.